The Contemporary Artwork Between Meaning and Cultural Identity - Paolo Martore (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The article intends to engage a critical review of some basic theoretical terms within Conservation strategies, especially in application to contemporary art.